2006
DOI: 10.1017/s0265021506000275
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided arterial cannulation in infants improves success rate

Abstract: The current pilot study suggests that ultrasound guidance is appropriate for radial artery catheter insertion, sharing many of the benefits of ultrasound-guided central vein catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 18 publications
2
100
1
3
Order By: Relevance
“…Schwemmer et al studied 30 infants and reported an improved success rate as well as fewer attempts in the US group as compared with the DP group. 15 On the other hand, in another prospective trial involving 152 children by Ganesh et al, US guidance did not facilitate faster cannulation of the radial artery. 24 A possible explanation for this may again relate to operator inexperience.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Schwemmer et al studied 30 infants and reported an improved success rate as well as fewer attempts in the US group as compared with the DP group. 15 On the other hand, in another prospective trial involving 152 children by Ganesh et al, US guidance did not facilitate faster cannulation of the radial artery. 24 A possible explanation for this may again relate to operator inexperience.…”
Section: Discussionmentioning
confidence: 90%
“…This may partly relate to the fact that comparatively few data exist on the potential advantages of US-guided radial artery insertion. While a number of studies before 2014 have reported an increase in first-attempt success rate, fewer attempts, and a shorter overall time for catheter insertion, 5,14,15 others found no advantage to using Doppler US, 16 save for a select group of patients with hemorrhagic shock. 17 In 2014, two systematic reviews/meta-analyses of randomized controlled trials dedicated to US-guided radial artery catheterization were published.…”
mentioning
confidence: 99%
“…Indeed, a number of studies have shown that US guidance has been proven to reduce complications and increase success rates for radial artery catheter placement. 3,5,[7][8][9][10] Our study is limited because we did not systematically record the US technique used (transverse, longitudinal, or static), the subject's body habitus, or the indication for arterial line placement. In addition, our assessment of pulse strength was subjective and intrapractitioner variability is possible.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Ultrasound guidance has been proven to be beneficial for radial artery catheter placement and can be utilized effectively by RTs. 1,[8][9][10][11][12] In the most recent systematic review and meta-analysis, which included 447 ultrasound attempts versus 455 palpation attempts, Gao et al 13 concluded that ultrasound significantly increased first-attempt success rate. For all subjects, ultrasound was associated with a risk ratio of 1.47 for first-attempt success; for adult subjects, the risk ratio was 1.38, and for pediatric subjects, the risk ratio was 1.73.…”
Section: Radial Artery Cannulationmentioning
confidence: 99%